2013
DOI: 10.1007/s10482-013-0100-5
|View full text |Cite
|
Sign up to set email alerts
|

The fermentation of sugarcane molasses by Dekkera bruxellensis and the mobilization of reserve carbohydrates

Abstract: The yeast Dekkera bruxellensis is considered to be very well adapted to industrial environments, in Brazil, USA, Canada and European Countries, when different substrates are used in alcoholic fermentations. Our previous study described its fermentative profile with a sugarcane juice substrate. In this study, we have extended its physiological evaluation to fermentation situations by using sugarcane molasses as a substrate to replicate industrial working conditions. The results have confirmed the previous repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 32 publications
0
18
1
1
Order By: Relevance
“…In exponentially growing cells of Dekkera bruxellensis the intracellular content of trehalose was quantified as low as 0·15 μ g Eq.glucose/10 7 cell, reaching near 2 μ g Eq.glucose/10 7 cell in stationary phase, which is in accordance with the lack of trehalose storage we have previously reported (Pereira et al . ). This lack of storage might be related either to limitation of synthesis or to a fast turnover of the metabolite in this yeast.…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…In exponentially growing cells of Dekkera bruxellensis the intracellular content of trehalose was quantified as low as 0·15 μ g Eq.glucose/10 7 cell, reaching near 2 μ g Eq.glucose/10 7 cell in stationary phase, which is in accordance with the lack of trehalose storage we have previously reported (Pereira et al . ). This lack of storage might be related either to limitation of synthesis or to a fast turnover of the metabolite in this yeast.…”
Section: Resultsmentioning
confidence: 97%
“…On the other hand, we did not observe trehalose accumulation when D. bruxellensis cells following exposure to high sugar concentration during molasses fermentation (Pereira et al . ). The lack of further activation indicated that in D. bruxellensis N‐trehalase does not respond to PKA pathway.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations